«КОДЕКС КУМАНИКУС» ВА БОШҚА ТУРКИЙ ҚЎЛЁЗМАЛАР ТИЛИ - Жафаров, Б.С. (SCIENCE and SOCIETY, 2016)
The article is devoted to the study of the peculiarities of transliteration of the Persian words in the ―Codex Cumanicus‖ which is considered to be one of the valuable manuscripts of the ancient Turkic people of Cumana and the research works plauned to do in future.
Keywords: “Toshbitig”; ―Devanu lugatit Turk”; “Kutadgu bilig”; ―Codex Cumanicus”; manuscript; Latin; Persian; Cuman; dictionary; transliteration